2019
DOI: 10.1111/vox.12861
|View full text |Cite
|
Sign up to set email alerts
|

Understanding donation frequency: insights from current plasma donors

Abstract: Background and Objectives Encouraging existing plasma donors to donate more frequently is a key objective for blood donation services committed to expanding yield through voluntary non‐remunerated plasmapheresis donation. This requires an understanding of donors’ perspectives on their current donation practice and how this relates to their knowledge and beliefs about the need for plasma. To explore this, Australian plasma donors were interviewed about how they arrived at the frequency at which they donate. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Consistent with Slootweg and colleagues [6], a small number of participants viewed being an anti‐D donor as an opportunity to make a bigger contribution as a donor because of who the recipient group was and the organizational need for anti‐D. This motivation may be similar to that identified in frequent plasma donors [13].…”
Section: Discussionsupporting
confidence: 57%
“…Consistent with Slootweg and colleagues [6], a small number of participants viewed being an anti‐D donor as an opportunity to make a bigger contribution as a donor because of who the recipient group was and the organizational need for anti‐D. This motivation may be similar to that identified in frequent plasma donors [13].…”
Section: Discussionsupporting
confidence: 57%
“…If possible, this plasma can be transfused into other infected patients to help them overcome viral infections. As plasma donation is a mature technology, and plasma transfusion is also a part of routine medical care, this proposal is the simplest and most feasible treatment under consideration (Thorpe, Masser, Nguyen, & Davison, 2020). At the same time, we also need to consider that this proposal is not a long-term solution because the growing number of cases is far outpacing the speed of the recovery.…”
Section: Promising Vaccines and Passive Antibodies From Convalescenmentioning
confidence: 99%
“…In Australia, one example of a country with a voluntary, non‐remunerated plasma donation system, plasma can be donated as often as every 2 weeks, yet fewer than 60% of new donors return to donate. Those who return give on average 4·1 plasma donations each year, with 50% of donors giving fewer than three plasma donations per year [7]. This is suboptimal, as repeat donations are safer and more cost‐effective than the recruitment of new donors [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is suboptimal, as repeat donations are safer and more cost‐effective than the recruitment of new donors [8]. Thorpe and colleagues found that most plasma donors adopt a flexible approach to donation frequency (only donating when it fits in their schedule) but also aspire to make more frequent donations [7]. Encouraging plasma donors to return to donate and donate more frequently are, therefore, important objectives for BCAs committed to improving plasma self‐sufficiency through voluntary non‐remunerated donations [9,10], and effective strategies to increase donation rates are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation